(untitled) (SAARC Journal of Agriculture, 2022)
People living in the char land area are considered the most disadvantaged group of people in Bangladesh. Considering the situation, a study was conducted to evaluate the feasibility of increasing income of char dwellers by following profitable cropping pattern. The treatments were CP1 (Farmers’ practice cropping pattern): Grass pea (BARI Khesari- 1)-Jute (var. JRO 524)-T. Aman (var. Swarna) and CP2 (Altered cropping pattern): Maize (var. Hybrid 981)-Jute (var. JRO 524)-T. Aman (var. Binadhan-11). A randomized complete block design with six dispersed replications was followed in this experiment. It was observed that the altered cropping pattern (CP2) produced higher rice equivalent yield (avg. 25.47 t ha-1), production efficiency (78.61 kgha-1 day-1) and gross margin US 3056.58 ha-1 than those of the farmer’s practice cropping pattern (CP1) rice equivalent yield (12.97 t ha-1), production efficiency (40.40 kgha-1 day- 1) and gross margin (Tk. 79,950 ha-1). Gross margin increased by 206% in altered cropping pattern compared with the existing cropping pattern, revealing that rabi crop based cropping pattern including flood damage escaping rice varieties Maize (var. Hybrid 981)-Jute (var. JRO 524)-T. Aman (var. Binadhan-11) is appropriate for getting higher productivity and profitability by the poor char dwellers of Jamalpur district in Bangladesh. SAARC J. Agric., 20(2): 121-131 (2022)